Augmenting DSVL Meta-Tools with Pattern Specification, Instantiation and Reuse - Li, Karen; Hosking, John; Grundy, John; Ly, Tony; Webb, Brian (Electronic Communications of the EASST, 2011)
This paper describes an approach for using patterns in domain-specific visual language (DSVL) meta-tools. Our approach facilitates DSVL development via high level design-for-reuse and design-by-reuse pattern modelling tools. It provides a simple visual pattern modelling language that is used in parallel with DSVL meta-model specifications for modelling and reusing DSVL structural and behavioural design patterns. It also provides tool support for instantiating and visualising structural patterns, as well as executing behavioural patterns on DSVL model instances.